Parasitic nematodes in stomachs of grey seals, Halichoerus grypus, and common seals, Phoca vitulina, along the Norwegian coast. - Bjørge, Arne (ICES, 1984)
The nematode infestation in stomachs of 55 grey and 127 common seals were examined in the period 1976-1980. The seals were caught in Norwegian coastal waters between 62° and 67° North. In 48 adult grey seals the infestation averaged 1 521 nematodes. In seven young grey seals (1-4 years old) the infestation was significantly lower, and averaged 519 nematodes. In 127 common seals (one year old and older) the infestation averaged 60 nematodes, and the infestation showed no significant increase with increasing age of the common seals. The number of nematodes did not differ significantly between the sexes of both species.